PEMBAGIAN LIFE JACKET DAN EDUKASI KESELAMATAN LAUT BAGI SISWA DI DESA NUMBING - Hanum, Athiifa; Widiyani , Heni; Sihombing, Sebastian Alboen; Hanum, Atiikah; Thahira, Atikah; Adhayanto, Oksep; Suryadi, Suryadi; Arjuna, Hendra; Irman, Irman; Intan, Dian Mustika (Universitas Mataram, 2025)
The community service program entitled